2009
DOI: 10.1007/s10533-009-9362-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil and stream water acidification in a forested catchment in central Japan

Abstract: Rapid industrialization in East Asia is causing adverse effects due to atmospheric deposition in terrestrial and freshwater ecosystems. Decreasing stream pH and alkalinity and increasing NO 3 -concentrations were observed throughout the 1990s in the forested Lake Ijira catchment in central Japan. We investigated these changes using data on atmospheric deposition, soil chemistry, stream water chemistry, and forest growth. Average atmospheric depositions (wet ? dry) of 0.83, 0.57, and 1.37 kmol ha -1 year -1 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…Due to increasing NO 3 À leaching from progressive N saturation, the greater affinity of protons for cation exchange sites in the soil will displace base cations. As base cation saturation is decreased, increased leaching of protons or mobilized aluminum with ensue leading to stream water acidification (Fang et al, 2011;Nakahara et al, 2010). In temperate catchments as well as in subtropical forests of southern China, $10.7 kg N ha À1 yr À1 of anthropogenic N input has been suggested as an N-saturation threshold Swaney et al, 2012;Zhang et al, 2013).…”
Section: Efficacy and Implications Of The N Budget-riverine Tn Flux Mmentioning
confidence: 99%
“…Due to increasing NO 3 À leaching from progressive N saturation, the greater affinity of protons for cation exchange sites in the soil will displace base cations. As base cation saturation is decreased, increased leaching of protons or mobilized aluminum with ensue leading to stream water acidification (Fang et al, 2011;Nakahara et al, 2010). In temperate catchments as well as in subtropical forests of southern China, $10.7 kg N ha À1 yr À1 of anthropogenic N input has been suggested as an N-saturation threshold Swaney et al, 2012;Zhang et al, 2013).…”
Section: Efficacy and Implications Of The N Budget-riverine Tn Flux Mmentioning
confidence: 99%
“…The high-risk areas in the maps also included some study sites at which surface water has been reported for the past several years. Surface water acidification in Lake Sawanoike (Yoshikawa et al 2000), Lake Yashagaike (MOEJ 2014), and some rivers in the north of Niigata Prefecture (Matsubara et al 2008) was assigned a relative risk category of IV or V. The areas corresponding to category V risk included the Lake Ijira watershed, a site where the effects of acid deposition on the significant water acidification have been reported (Yamada et al 2007;Nakahara et al 2010). Thus, the map of case F may serve as a risk map for surface water acidification.…”
Section: Relative Risk Maps and Their Sensitivities To Different Weightsmentioning
confidence: 99%
“…Thus, the map of case F may serve as a risk map for surface water acidification. The soil acidification risk was also evaluated at two sites, Gifu and Ishikawa, where long-term soil acidification has been recorded (Nakahara et al 2010 andMOEJ 2014, respectively). As a result, the sites fall into high-risk categories in maps A and E, which corroborates the idea that soil acidification is more closely related to soil sensitivity than to bedrock sensitivity.…”
Section: Relative Risk Maps and Their Sensitivities To Different Weightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshwaters continue to suffer from acidification in many parts of the world (e.g., Kowalik et al, 2007;Lawrence et al, 2008;Nakahara et al, 2010) due to a combination of present-day or historic high acid deposition and the occurrence of soils with low buffering capacity, resulting in adverse impacts on the aquatic ecology (Baldigo et al, 2009;Harriman et al, 1987). Surface water acidification is predominantly caused by the transfer of anthropogenically-derived strong acids and acid-forming substances, in particular sulphur dioxide (SO 2 ), nitrogen oxides (NO x ), ammonia (NH 3 ) and the particulate acidifying compounds sulphate (SO 4 ) and nitrate (NO 3 ), from the atmosphere via deposition to the earth's surface (Driscoll et al, 2001).…”
Section: Introductionmentioning
confidence: 99%